Analisa Stray Losses Pada Struktur Transformator Daya Satu Fasa 275 Kv 83.3 MVA - Saepudin, Asep Saepudin (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2020)
Background The jurnal discusse stray losses are generated by eddy current losses in the single phase transformer construction parts, such as Main tank, cover,core clamp and flitch plate. Stray losses can’t measurement direct and only calculated. Aim This study is to accurate calculated stray losses are generated in the single phase transformer construction parts in order to get more accurate calculated compared with measured and to know calculation versus measurement and versus simulation. Method This study using 3D Finite Element Metode with basis software ANSYS in the single phase transformer construction parts Result The stray losses in the single phase transformer construction parts, so that it hasn’t a simple stray losses divided by 3 compared to three phase transformers with same power and voltage. Conclusion Base on this study the total stray losses around 30%-37% from Load Losses and impove approxi-mately 9% compared between existing calculation and this simulation study versus measurement.